(untitled) (Academia Science Repository, 2023)
In this article, the formation of the professional competence of future educators is a pedagogical problem, the analysis of the work carried out on the Competence requires constantly enriching one’s knowledge, learning new information, feeling the demands of this day and age, the ability to search for new knowledge, process it and apply it in one’s practical work. A competent specialist knows how to use the methods and methods that he has mastered in solving problems, which are suitable for this particular situation, he can selectively use the methods that are suitable for the current situation, reject those that are not appropriate, acquires skills such as critical thinking. Competent approach in pedagogy is not a completely new phenomenon, but its tributaries exist in continuously developing educational processes, and they were formed step by stepformation of professional competence was expressed.